Working Student Nurses: A Husserlian Phenomenology of Study-Work Balance - Sebullen, Michael; Bantali, Jesse (Journal of Interdisciplinary Perspectives, 2025)
This research examined the experiences of 12 nursing students who are working while studying, using Husserlian phenomenology as a framework. The study was conducted at Baguio Central University and employed a qualitative approach, including semi-structured interviews and phenomenological reduction, to uncover the core aspects of their experiences. The participants were twelve fourth-year nursing students who were balancing their academic responsibilities with employment. The data collected were transcribed and analyzed thematically using NVivo software, which facilitated the systematic coding of transcripts and helped identify emerging themes and patterns across participants’ accounts, incorporating ideas from the Phenomenology of Perception and Embodiment. The findings indicated that: (1) working nursing students commonly experience the challenges of balancing roles and sacrificing self-care; (2) they use time management as a resilience strategy; (3) they face health strain and emotional exhaustion due to juggling work and study; (4) their views on professional readiness are influenced by support systems and grounding practices; and (5) financial motivation and professional growth help them remain resilient in managing both work and study. Their coping strategies included establishing time-based routines, engaging in spiritual practices, and finding joy through short breaks and leisure activities. Despite facing academic fatigue, emotional stress, and physical tiredness, the participants exhibited a strong sense of agency and were developing their professional identities. The study concludes that while working while studying is challenging, it fosters growth and a goal-oriented mindset among nursing students. They cope by effectively managing their time, maintaining a positive outlook, seeking support, and relying on their faith. Balancing both responsibilities impacts their health and academic performance, although some students become more motivated to succeed. This experience enhances their confidence and skills while also exposing them to the harsh realities of the nursing profession. A sense of purpose, self-confidence, drives their resilience, and the determination to persevere despite fatigue.